Fluxes of lactate into, from, and among gap junction-coupled astrocytes and their interaction with noradrenaline - Hertz, Leif; Gibbs, Marie E.; Dienel, Gerald A. (Frontiers in Neuroscience, 2014)
Lactate is a versatile metabolite with important roles in modulation of brain glucose utilization rate (CMRglc), diagnosis of brain-injured patients, redox- and receptor-mediated signaling, memory, and alteration of gene transcription. Neurons and astrocytes release and accumulate lactate using equilibrative monocarboxylate transporters that carry out net transmembrane transport of lactate only until intra- and extracellular levels reach equilibrium. Astrocytes have much faster lactate uptake than neurons and shuttle more lactate among gap junction-coupled astrocytes than to nearby neurons. Lactate diffusion within syncytia can provide precursors for oxidative metabolism and glutamate synthesis and facilitate its release from endfeet to perivascular space to stimulate blood flow. Lactate efflux from brain during activation underlies the large underestimation of CMRglc with labeled glucose and fall in CMRO2/CMRglc ratio. Receptor-mediated effects of lactate on locus coeruleus neurons include noradrenaline release in cerebral cortex and c-AMP-mediated stimulation of astrocytic gap junctional coupling, thereby enhancing its dispersal and release from brain. Lactate transport is essential for its multifunctional roles.